THEORETICAL ASPECTS OF MODELING OF INFORMATION STREAMS IN COMPANY LOGISTICS - V. Skitsko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The work investigates the existing models of information streams; offers hierarchical levels of modeling of information streams; for general case it describes the possible breaches that may take place in the process of information streams flow; offers the ways of using of the corresponding instruments of modeling for solving the number of problems connected with the analysis of information streams.